Lessons in exile - Pereda, Carlos, 1944- (Value Inquiry Book Series, 2018)
This book, winner of the 2007 Siglo XXI International Essay Prize, is unique in its approach to exile and offers remarkable insights into the subject. It discusses both human nature and the phenomenon of exile with depth and exactness from the combined perspectives of philosophy, morality, politics, anthropology, and history. After retracing the lessons learned through diverse experiences of exile from antiquity to modern times, it uses poetry as metatestimony to examine exile, subjectivity, and the many moral and political implications involved. The result is a series of thoughtprovoking connections between exile and the way we assume our lives.